If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y=41+3
We move all terms to the left:
y-(41+3)=0
We add all the numbers together, and all the variables
y-44=0
We move all terms containing y to the left, all other terms to the right
y=44
| 6u-9u+9=-3-u | | (2x-1)^3/4=27 | | 13-3d=5 | | 8.4=3x | | 15x+27=-49+61 | | -5(x-1)+3x=7(x+1) | | 11+4k-8k=3-8k | | a3=−18 | | -13(2m-1)=65 | | 17=3(r+1)-4r | | d=3.5=1 | | 2/9=4/x-8 | | 17=3(r+1)-4r | | 10x+10x+90=610 | | 17x+1=1+17x | | -33=-4x-5 | | 2(5x+9)=3(5+3x) | | 4-2(y-3)=16 | | 2(2c+4)-1=15 | | 1344=17.6x+1090.6 | | 15+13=x | | 2x+10=53 | | -8b-9=6b+9 | | (3x-15)(3x+25)4x=x | | -3=5-3a+4 | | d–100=100 | | 3b-11b+10=-39 | | 2x+x+4+x=180 | | 11x+2x=-39 | | (3x-15)=(3x+25)4x | | 12x–43-10x=-83 | | 7b+12=9 |